(untitled) (Journal of National Institute of Neurosciences Bangladesh, 2023)
Background: Detection of aneurysms among spontaneous subarachnoid haemorrhagic patients is a crucial issue for management. Objectives: The purpose of the present study was to compare the findings of 3D-computed tomographic angiography with digital subtraction angiography for detection of aneurysms among spontaneous subarachnoid haemorrhagic patients. Methodology: This comparative cross-sectional study was carried out in the Department of Neurosurgery and Cath Lab of Dhaka Medical College Hospital (DMCH), Dhaka, Bangladesh in collaboration with private diagnostic centre from September 2013 to February 2015 for a period of six (06) months. Adult patients diagnosed as a case of spontaneous SAH based on clinical features and confirmed by plain CT evidence of subarachnoid blood were included as study cases. Then both CTA and DSA were done in order to detect the cause of bleeding and make a treatment planning. All spiral CTAs were performed on a helical CT-Scan. Four vessels DSA were performed via a femoral approach in DMCH Cath Lab. Result: A total number of 37 patients presented with spontaneous subarachnoid haemorrhage were recruited for this study. CT Angiogram revealed aneurysm in 30(81.08%) patients. AVM found in 02(05.41%) patients and in 5(13.51%) patients CTA was negative for any abnormality. DSA of 37 patients revealed aneurysm in 32(86.49%) patients, AVM in 02(05.41%) patients and negative findings in 03(8.11%) patients. In CT Angiogram 25(67.57%) patients had single aneurysm. In DSA, 27(72.97%) patients had single aneurysm. The mean of the size of the aneurysms in CTA and DSA were in 6.70±3.04 mm and 6.75±2.94 mm (p>0.05). The mean of the neck width of the aneurysms in CTA and DSA were 3.86±2.06 mm and 3.41±1.67 mm (p>0.05). All aneurysm detected in CTA were also revealed in DSA. Conclusion: In conclusion the size, neck width and the location of aneurysm are detected in CTA and DSA equally without any statistical significant difference. Journal of National Institute of Neurosciences Bangladesh, July 2022;8(2):121-125